UTILIZATION OF DSLR CANON 1200D CAMERA FOR VARIABLE STAR PHOTOMETRIC OBSERVATION - Wibowo, Ari
Currently, variable star research in Indonesia is still not very popular, because only the Bosscha Observatory (abbreviated OB) that has contributed to the observation of variable stars, although there were actually many other observatories that have been built in Indonesia. Most of the research conducted by observatories other than OB has been still focused on rukyatul hilal, and measurement of sky brightness with SQM. There were 6 school-based observatories and 4 universitybased observatories equipped with telescopes, detectors and other instruments. In fact, the availability of instruments and equipment owned by private observatories in Indonesia is very supportive for other observation activities, namely variable star photometry. It's just that according to the managers of several observatories it has not been able to optimize the existing equipment for variable star photometric research because there are several constraint factors, including the lack of ability to optimize existing instruments for variable star research, also the lack of knowledge that can help explain good variable stars in theory and observation. Observation of star variables themselves have focused on variable stars with short periods where short periods of time do not require large enough memory and are not complicated in processing. The photometric technique used was differential photometry. While the processing itself used software that was commonly available to astronomers and private observatories in Indonesia including IRIS devices, Stellarium Software and digiCamControl software. The technique of retrieving data and the results of data processing in this thesis is expected to be a reference for enriching the treasure of research in private observatories in Indonesia.